1998
DOI: 10.7863/jum.1998.17.12.743
|View full text |Cite
|
Sign up to set email alerts
|

Bladder distention and pyelectasis in the male fetus: causes, comparisons, and contrasts.

Abstract: The objective of this paper was to determine if prenatal sonographic findings can accurately differentiate between the causes of bladder distention and pyelectasis in the male fetus. Twenty‐one cases were evaluated for the presence of oligohydramnios, posterior urethral dilation, bladder wall thickening, urachal patency, cortical thinning, cortical cysts, and increased renal echogenicity. Postnatal diagnosis included posterior urethral valves (10 cases), prune belly syndrome (four cases), vesicoureteral reflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The authors documented that the simultaneous presence of oligohydramnios and increased renal echogenicity was highly predictive of infravesical obstruction with 100% sensitivity and 93% specificity. Montemarano et al [9] reported as most suggestive of PUV the presence of oligohydramnios, progressive bladder thickening and a dilated posterior urethra. Nevertheless, the data obtained in all of these studies were submitted to univariate analyses that did not evaluate the combined effects of two or more factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors documented that the simultaneous presence of oligohydramnios and increased renal echogenicity was highly predictive of infravesical obstruction with 100% sensitivity and 93% specificity. Montemarano et al [9] reported as most suggestive of PUV the presence of oligohydramnios, progressive bladder thickening and a dilated posterior urethra. Nevertheless, the data obtained in all of these studies were submitted to univariate analyses that did not evaluate the combined effects of two or more factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dilatation was considered to be present if the maximum anteroposterior diameter of the fetal renal pelvis was 65 mm. Bladder distention (megacystis) was defined as an abnormally large appearing bladder with failure of the bladder to empty over a period of time greater than 45 min [9]. Oligohydramnios was determined on the basis of the amniotic fluid index [11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Montemarano (13), describe dilatación de la uretra posterior en dos de 4 casos de síndrome de Prune belly, observadas con ecografías obstétricas a las 16 y 19 semanas de gestación respectivamente. Osborne y col (14), describen que la dilatación de las vías urinarias resulta de la obstrucción a diferentes niveles, pero se dan casos de dilatación sin evidencia de obstrucción.…”
Section: Discussionunclassified
“…In the second and third trimester, the obstruction at the level of bladder neck Previous studies found this ultrasonographic sign very specific to LUTO especially in a fetus with posterior urethral valves (23,24). However, a retrospective study showed that it was only present in 51.6% of fetus with proven posterior urethral valve and could be seen in 34.8% of other non-obstructive pathologies including vesicoureteric reflux and primary megaureter (25).…”
Section: Iii) Diagnosis Of Lutomentioning
confidence: 99%